2016
DOI: 10.1007/s10803-016-2755-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Self-Directed and Therapist-Assisted Telehealth Parent-Mediated Intervention for Children with ASD: A Pilot RCT

Abstract: This pilot RCT compared the effect of a self-directed and therapist-assisted telehealth-based parent-mediated intervention for young children with ASD. Families were randomly assigned to a self-directed or therapist-assisted program. Parents in both groups improved their intervention fidelity, self-efficacy, stress, and positive perceptions of their child; however, the therapist-assisted group had greater gains in parent fidelity and positive perceptions of child. Children in both groups improved on language m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
214
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(240 citation statements)
references
References 44 publications
(46 reference statements)
19
214
0
Order By: Relevance
“…Several recent studies have demonstrated the initial efficacy of evidence-based, parent-mediated autism interventions when delivered by computer or over the internet, with or without therapist assistance [14-17]. One such program, ImPACT Online, is an interactive website that teaches parents to promote their child’s social communication within the context of play and daily routines [14,18,19]. The content was modified from Project ImPACT, an evidence-based social communication curriculum for young children with ASD [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have demonstrated the initial efficacy of evidence-based, parent-mediated autism interventions when delivered by computer or over the internet, with or without therapist assistance [14-17]. One such program, ImPACT Online, is an interactive website that teaches parents to promote their child’s social communication within the context of play and daily routines [14,18,19]. The content was modified from Project ImPACT, an evidence-based social communication curriculum for young children with ASD [20].…”
Section: Introductionmentioning
confidence: 99%
“…ImPACT Online can be delivered as a self-directed intervention or with therapist assistance via videoconferencing. A recent pilot randomized controlled efficacy trial comparing the two formats demonstrated positive effects on parent learning and child social communication skills for both groups, although there was an added benefit of therapist assistance on some parent and child outcomes [14,18]. Although engagement with the program website was significantly higher among parents in the therapist-assisted group, parents in the self-directed group engaged with the program at a relatively high rate, with 69% completing the program [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, perhaps the need for additional therapist support is dependent on the condition to be treated or on user characteristics. While some studies clearly support the superiority of clinician guidance (Ingersoll, Wainer, Berger, Pickard, & Bonter, 2016;Kleiboer et al, 2015), it is also possible that it is sufficient to provide automated reminders and only provide access to a clinician when the user asks for it (Titov et al, 2013). Some studies indicate that support does not need to be therapeutically oriented, but can be mainly practical and technical (Titov et al, 2010).…”
Section: Effective Components Of Web-based Interventionsmentioning
confidence: 99%
“…The few available interactive programs for parents have been largely designed for parents of infants , parents of children with traumatic brain injury (Wade, Carey, & Wolfe, 2006) or other health conditions (Ingersoll et al, 2016), and parents with mental health problems (Jones, Calam, et al, 2014;Kaplan, Solomon, Salzer, & Brusilovskiy, 2014). However, there is a lack of randomised controlled trials, particularly in the area of prevention and treatment of child emotional and behaviour problems.…”
Section: Web-based Interventions For Parenting Supportmentioning
confidence: 99%
See 1 more Smart Citation